Resources and student achievement: Evidence from a Swedish policy reform - Peter Fredriksson; Björn Öckert (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This paper utilizes a policy change to estimate the effect of teacher density on student performance. We find that an increase in teacher density has a positive effect on student achievement. The baseline estimate – obtained by using the grade point average as the outcome variable – implies that resource increases corresponding to the class-size reduction in the STAR-experiment (i.e., a reduction of 7 students) improves performance by 2.6 percentile ranks (or 0.08 standard deviations). When we use test score data for men, potentially a more objective measure of student performance, the effect of resources appears to be twice the size of the baseline estimate.
Keywords: I21; I28; J24; 330; Student performance; teacher/student ratio; policy reform; differences-in-differences; Bildungsreform; Schulpolitik; Allokation; Bildungsniveau; Schweden